2011
DOI: 10.1016/j.jacc.2011.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Quadriceps Training Increases Maximal Exercise Capacity in Chronic Heart Failure

Abstract: Objectives This study sought to elucidate the mechanisms responsible for the benefits of small muscle mass exercise training in patients with chronic heart failure (CHF). Background How central cardiorespiratory and/or peripheral skeletal muscle factors are altered with small muscle mass training in CHF is unknown. Methods We studied muscle structure and oxygen (O2) transport and metabolism at maximal cycle (whole body) and knee-extensor exercise (KE) (small muscle mass) in 6 healthy controls and 6 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
142
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(157 citation statements)
references
References 40 publications
(50 reference statements)
12
142
1
2
Order By: Relevance
“…Moreover, our study indicates a probable role of the blunted muscle capillarisation response to training in the reduced V9O 2 SL improvement in the COPD patients, as angiogenesis has also shown an impact on the improvement in V9O 2 SL in two other chronic diseases: CHF [41] and peripheral arterial disease [42]. Our finding of lower improvement in the capillary-to-fibre ratio thus appears to be clinically significant.…”
Section: Discussionsupporting
confidence: 53%
“…Moreover, our study indicates a probable role of the blunted muscle capillarisation response to training in the reduced V9O 2 SL improvement in the COPD patients, as angiogenesis has also shown an impact on the improvement in V9O 2 SL in two other chronic diseases: CHF [41] and peripheral arterial disease [42]. Our finding of lower improvement in the capillary-to-fibre ratio thus appears to be clinically significant.…”
Section: Discussionsupporting
confidence: 53%
“…Further studies in heart failure have demonstrated that impaired diffusional transport of oxygen may be amenable to an exercise rehabilitation programme [15], but a recent detailed assessment of the exercise haemodynamic changes following a comprehensive exercise programme did not report on these aspects [16]. Impairment of muscle flow has not been evaluated in pulmonary hypertension, but may be an additional contributing factor, as previously demonstrated in heart failure patients [15,17].…”
Section: Cardiovascular Response To Exercise In Pahmentioning
confidence: 99%
“…Esposito and colleagues (36) have demonstrated that HF severely reduces muscle oxygen diffusion conductance (DO 2 m), helping to explain why increasing O 2 delivery to skeletal muscle via vasodilators in HF might not yield expected increases in muscle O 2 consumption during aerobic exercise (Figure 2). The impaired DO 2 m may also help account for poor muscle function and exercise intolerance in both HFrEF and HFpEF.…”
Section: Peripheral Mechanisms Of Exercise Intolerance In Heart Failurementioning
confidence: 99%